Experimental Design Factorial Parameters of Honey Water Content Levels to Improve Honey Processing Productivity - Denny Nurkertamanda; Mohammad Habiel Baihaqi; Yusuf Widharto (Logic : Jurnal Rancang Bangun dan Teknologi, 2022)
In producing honey products, must meet all SNI quality standards (8665:2018), one of which is honey water content of less than 22%. Honey from farmers has a moisture content of more than 22% so the water content must be reduced. On of the technique that use in a company to meet those standard uses a dehumidification system combined with air conditioning and a honey rain device. With the current machine configuration, the required honey moisture reduction process time is 11 days. This study focuses on finding a combination of degrees Celsius temperature factor and relative humidity percentage factor that results in the optimal rate of reduction in water content. The results showed that temperature and relative humidity each had an effect on the rate of decrease in the water content of honey and no interaction effect was found between the factors of temperature and relative humidity on the rate of decrease in the water content of honey. The combination of selected temperature and relative humidity factors, namely 27℃ and 40%, in the most optimal rate of decrease in water content with an average of 0.416667% per hour. When compared with the combination of temperature and relative humidity in the company, namely 30°C and 60%, the selected treatment combination can reduce the processing time for reducing the honey moisture content and increases productivity by 50%.